2001
DOI: 10.1002/1521-4141(200112)31:12<3649::aid-immu3649>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for CD28 co-stimulation is lower in SHP-1-deficient T cells

Abstract: This study provides biochemical and functional evidence pertaining to the role of the intracellular protein tyrosine phosphatase, SHP‐1, in influencing thresholds for TCR activation. Although the loss of SHP‐1 in thymocytes from motheaten mice had minimal effects on the initial rise of cytosolic Ca2+ concentration following TCR triggering, the post‐stimulation equilibrium levelsof Ca2+ were consistently elevated. In keeping with a SHP‐1 effect on PLCγ function, IP3 generation was increased in SHP‐1 deficient t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Similarly, the SH2-domain-containing protein tyrosine phosphatase 1 (SHP-1) can reduce costimulation as observed in SHP-1-deficient CD4 + thymocytes. 106,107 In keeping with this, SHP-1 associates in a complex with Vav1, Grb-2 and Sos1. 105 The suppressor cytokine IL-10 has also been reported to activate SHP-1 and in the process, suppress PI3K binding to CD28.…”
Section: Cd28 and Negative Regulationmentioning
confidence: 59%
“…Similarly, the SH2-domain-containing protein tyrosine phosphatase 1 (SHP-1) can reduce costimulation as observed in SHP-1-deficient CD4 + thymocytes. 106,107 In keeping with this, SHP-1 associates in a complex with Vav1, Grb-2 and Sos1. 105 The suppressor cytokine IL-10 has also been reported to activate SHP-1 and in the process, suppress PI3K binding to CD28.…”
Section: Cd28 and Negative Regulationmentioning
confidence: 59%
“…Among these phosphatases, only PTEN and SHP-1, which were also shown to reduce IL-2 production (76, 78), have been linked to autoimmune phenomena. Specifically, mice carrying PTEN gene mutations present impaired Fas-mediated apoptosis and develop autoimmune disease (81), while SHP-1-deficient mice produce pathogenic autoantibodies and suffer from lupus-like glomerulonephritis (76). In addition, autoimmune phenomena are documented in patients with Cowden syndrome, a disease caused by germline PTEN mutations (82).…”
Section: Discussionmentioning
confidence: 99%
“…In order to mimic clinical adoptive transfer strategies, T-cells were subject to three rounds of in vitro antigen stimulation prior to transfer. Although this system might appear to fail to take advantage of the increased antigen-dependent proliferation of naive SHP-1 null T-cells described by Sathish et al [37,61], the authors observed increased proliferation of transferred effector T-cells in response to tumour in vivo , reduced apoptosis and improved survival of SHP-1 −/− T-cells, and, ultimately improved clearance of leukaemia. This demonstrates that abrogation of SHP-1 is beneficial in effector T-cells, not just in naive T-cells, and therefore knocking out SHP-1 in in vitro -activated, genetically modified T-cells would still add value to adoptive transfer strategies.…”
Section: Shp-1 Abrogation In Cancer Therapymentioning
confidence: 99%
“…In the absence of SHP-1, CD8 T-cells form more stable and durable synapses with antigen presenting cells (APCs) [37]. This leads to reduced activation thresholds and increased proliferation [38], which is beneficial for any kind of adoptive transfer strategy for two reasons: firstly, numbers of T-cells available for transfer are often limited, especially where genetic modification is involved; and, secondly it is known that the balance of regulatory T-cells to effector T-cells is key in tumour progression [39], so any modification that can bias towards increased effector T-cells is likely to improve treatment efficacy (Figure 2). It is worth noting that SHP-1 has also been shown to be inhibitory to T regulatory cells [40], and therefore inhibition of SHP-1 in these cells leads to increased suppressor function.…”
Section: Src Homology 2 Domain-containing Protein Tyrosine Phosphatasmentioning
confidence: 99%